# Tell me what have I found?

## Main Question or Discussion Point

One of the basic rules of lever are:
1) F1 * D1 = F2 * D2
F = force; D=distance; 1 and 2 are for states 1 and 2 or objects 1 and 2;
The 3rd Newton's law is a special case when D1 = -D2.
1) can be transformed into:
2) F1 / D2 = F2 / D1 = (F1 + F2) / (D1 + D2)
2.1) F1 * F2 = sqr(F1 + F2) * D1 * D2 / sqr(D1 + D2)
If F is caused by mass it's
3) F1 = L * M1 and F2 = L * M2
as masses attract.
If F is caused by charge it's
4) F1 = K * Q1 and F2 = - K * Q2
as charges repel.
- K and L are constants;
If both
5) F1 = L * M1 + K * Q1 and F2 = L * M2 - K * Q2

6) (L * M1 + K * Q1) * (L * M2 - K * Q2) = F1 * F2 = sqr(F1 + F2) * D1 * D2 / sqr(D1 + D2)

7) sqrt{L * L * (M1 / D1) * (M2 / D2) - K * K * (Q1 / D1) * (Q2 / D2) + L * K * (Q1 * M2 - M1 * Q2) / (D1 * D2)} * (D1 + D2) = (F1 + F2)

If Q1 = Q2 = 0 then sqrt{L * L * (M1 / D1) * (M2 / D2)} * (D1 + D2)= Gravity force = Total force in the system

If M1 = M2 = 0 then sqrt{- K * K * (Q1 / D1) * (Q2 / D2)} * (D1 + D2)= Coulombian force = Total force in the system

So what represents sqrt{L * K * (Q1 * M2 - M1 * Q2) / (D1 * D2)} * (D1 + D2)?